VIBRATION ANALYSIS AND OPTIMAL DESIGN OF LIGHT TRUCKS FUEL FILTER BRACKET - WU Hao; ZHONG ZiFeng (Jixie qiangdu)
Aiming at solving the cracking problem of a light card fuel filter bracket in the vehicle road test. Firstly,each road vibration acceleration were collected,the test results show that the washboard road vibration acceleration is the largest.Secondly,the frame end was taken an exciting point and the measured frequency domain signal were load,the bracket was vibration analyzed based frequency response method,the analysis results show that the bracket Z direction maximum von Mises stress value exceed the yield strength of the material. It is located at the circular tube bend and it was consistent with the actual failure position. Lastly,the fuel filter bracket was multi-objective optimization analyzed based on Isight platform integrated CATIA,HYPERMESH and NASTRAN by adopting non-dominated sorting genetic algorithm. So the circular tube optimal parameters are obtained and the bracket maximum stress value are lower than the allowable stress after optimization. The optimization effects are obvious and it could meet fatigue strength performance requirements. The optimization scheme had passee the road test,so the cracking problem was successfully solved. The analysis method wad integrated with road test,finite element technology,frequency response method and vehicle reliability road test,the advanced reference and practical engineering application for the similar brackets vibration analysis and optimization design were provided.